A city divided : the racial landscape of Kansas City, 1900-1960 - Schirmer, Sherry Lamb, 1947- (University of Missouri Press, 2002)
"A City Divided traces the development of white Kansas Citians' perceptions of race and examines the ways in which those perceptions shaped both the physical landscape of the city and the manner in which Kansas City was policed and governed. Because of rapid changes in land use and difficulties in suppressing crime and vice in Kansas City, the control of urban spaces became an acute concern, particularly for the white middle class, before race became a problematic issue in Kansas City." "These racial perceptions continue to shape race relations in Kansas City and elsewhere. This study demystifies these perceptions by exploring their historical context. While there have been many studies of the emergence of ghettos in northern and border cities, and others of race, gender, segregation, and the origins of white ideologies, A City Divided is the first to address these topics in the context of the dynamic, urban society in the Midwest."--Jacket